Comparative Genomics Reveals a Single Nucleotide Deletion in pksP That Results in White-Spore Phenotype in Natural Variants of Aspergillus fumigatus - Gibbons, John G.; D’Avino, Paolo; Zhao, Shu; Cox, Grace W.; Rinker, David C.; Fortwendel, Jarrod R.; Latge, Jean-Paul (Frontiers in Fungal Biology, 2022)
Aspergillus fumigatus is a potentially deadly opportunistic human pathogen. A. fumigatus has evolved a variety of mechanisms to evade detection by the immune system. For example, the conidium surface is covered in a layer of 1,8-dihydroxynaphthalene (DHN) melanin which masks the antigen macrophages use for recognition. DHN melanin also protects conidia from ultraviolet radiation and gives A. fumigatus conidia their characteristic green-grayish color. Here, we conducted genomic analysis of two closely related white-spore natural variants of A. fumigatus in comparison to two closely related green-spore isolates to identify a genetic basis of the white-spore phenotype. Illumina whole-genome resequencing data of the four isolates was used to identify variants that were fixed in the white-spore isolates and different from both the green-spore isolates and the Af293 reference genome (which is also a green-spore isolate). We identified 4,279 single nucleotide polymorphisms and 1,785 insertion/deletions fitting this pattern. Among these, we identified 64 variants predicted to be high impact, loss-of-function mutations. One of these variants is a single nucleotide deletion that results in a frameshift in pksP (Afu2g17600), the core biosynthetic gene in the DHN melanin encoding gene cluster. The frameshift mutation in the white-spore isolates leads to a truncated protein in which a PP-binding domain is interrupted and an additional PP-binding domain and a thioesterase domain are omitted. Growth rate analysis of white-spore and green-spore isolates during optimal temperature (37°C) and thermal stress (48°C) revealed that white-spore isolates grow slower than the closely related green-spore isolates, and that white-spore isolates are thermosensitive, as they did not grow during the thermal stress condition. Overall, we used comparative genomics to identify the mutation and protein alterations responsible for the A. fumigatus white-spore phenotype.